Evaluation of groundwater suitability for domestic, irrigational, and industrial purposes: A case study from Thirumanimuttar river basin, Tamilnadu, India - Vasanthavigar, M.; Srinivasamoorthy, K.; Prasanna, Mohan (Springer Netherlands, 2012)
The Thirumanimuttar sub-basin forms an important groundwater province in south India, facing serious deficiency in both quality and quantity of groundwater due to increased demand associated with rapid population explosion, agricultural growth and industrial activities. A total of 194 groundwater samples were collected and 15 water quality parameters were analyzed using standard procedures. Na+, Cl-, Ca2+, HCO -3, Mg2+ and SO 2-4 concentration ions are more dominant in both seasons. The total dissolved solids and electrical conductivity was observed good correlation with Na+, Cl-, HCO -3, Ca2+, Mg2+, Cl-, PO 3-4 and NO -3 ions indicating dominance of plagioclase feldspar weathering, anthropogenic input and over drafting of groundwater irrespective of seasons. The Hill–Piper diagram indicates alkaline earths exceed the alkalis, an increase of weak acids was noted during both the seasons. For assessing the groundwater for irrigation suitability parameters like total hardness, sodium adsorption ratio, residual sodium carbonate (RSC), permeability index, and sodium percentage are also calculated. Permanent hardness was noted in higher during both the seasons due to discharge of untreated effluents and ion exchange process. The RSC indicates 56% of the samples are not suitable for irrigation purposes in both seasons, if continuously used will affect the crop yield. From the results, nearly 72% of the samples are not suitable for irrigation.